Genetic variation in Tertiary relics: The case of eastern‐Mediterranean Abies (Pinaceae) - Hrivnák, Matúš; Paule, Ladislav; Krajmerová, Diana; Kulaç, Şemsettin; Şevik, Hakan; Turna, İbrahim; Tvauri, Irina; Gömöry, Dušan (Wiley, 2017)
AbstractThe eastern‐Mediterranean Abies taxa, which include both widely distributed species and taxa with minuscule ranges, represent a good model to study the impacts of range size and fragmentation on the levels of genetic diversity and differentiation. To assess the patterns of genetic diversity and phylogenetic relationships among eastern‐Mediterranean Abies taxa, genetic variation was assessed by eight nuclear microsatellite loci in 52 populations of Abies taxa with a focus on those distributed in Turkey and the Caucasus. Both at the population and the taxon level, the subspecies or regional populations of Abies nordmanniana s.l. exhibited generally higher allelic richness, private allelic richness, and expected heterozygosity compared with Abies cilicica s.l. Results of both the Structure analysis and distance‐based approaches showed a strong differentiation of the two A. cilicica subspecies from the rest as well as from each other, whereas the subspecies of A. nordmanniana were distinct but less differentiated. ABC simulations were run for a set of scenarios of phylogeny and past demographic changes. For A. ×olcayana, the simulation gave a poor support for the hypothesis of being a taxon resulting from a past hybridization, the same is true for Abies equi‐trojani: both they represent evolutionary branches of Abies bornmuelleriana.
Keywords: Abies equi-trojani; Approximate Bayesian Computation; Abies nordmanniana; Abies cilicica; Abies bornmuelleriana; phylogeny; diversity; Original Research; 15. Life on land